Implementation of Outing Class to Stimulate Student Motivation - Paulina Bewu Lele; Sukarman Hadi Jaya Putra; Yohanes Bare; Yohanes Nong Bunga (Yayasan Ahmar Cendekia Indonesia, 2023)
An interesting teaching and learning process will further motivate students to be active in learning. Processes that are standard and tend to be rigid make students bored and disinterested in learning, moreover science learning materials usually keep students motivated. The concept of contextual science learning needs to be done, so that they experience real learning more. One of them is learning with a contextual approach is outing class. Learning that is directly in contact with nature. This PKM activity involved 25 grade 4 students at SDN Napungbiri Pante, Waigete District, and Sikka Regency. PKM is carried out by involving students to be actively involved in learning with the outing class model. The results of this PKM activity show that the level of student participation reaches 100% with very good motivation, namely 94%. These results indicate that outing class activities have a good impact on increasing student motivation, which in the end will have implications for increasing students' cognitive scores.